Diagnosis and Management of Paraquat Intoxication - Lydia Sarah Shabrina; Armen Ahmad; Fadrian Fadrian (HM Publisher, 2023)
Paraquat poisoning is a clinical toxicological emergency due to the active ingredient of this type of herbicide, gramoxone, with a high mortality rate due to high toxicity, and no antidote has yet been found. Paraquat intoxication can cause multi-organ failure if ingested accidentally or spontaneously because paraquat quickly produces ROS (reactive oxygen species), which causes cell damage through lipid peroxidation, NF-kB activation, mitochondrial damage, and apoptosis in many organs. This results in rapid nephrotoxic and hepatotoxic as well as pulmonary fibrosis. Clinical manifestations depend on the level of paraquat ingested, which can be in the form of local toxicological and systemic toxicological effects. Laboratory tests for diagnosing paraquat toxicity can be used for toxicological analysis of plasma and urine. Management of paraquat intoxication is primarily to remove paraquat from the gastrointestinal tract (prevent absorption) by using activated charcoal, changing the toxicokinetics of the herbicide (increasing serum paraquat elimination) by hemoperfusion and hemodialysis, as well as modifying its toxicodynamics with anti-inflammatory drugs such as immunosuppressants (corticosteroids and cyclophosphamide) and antioxidants (N -acetylcysteine and vitamin C).